1976
DOI: 10.1203/00006450-197605000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ketonemia and Seizures: Metabolic and Anticonvulsant Effects of Two Ketogenic Diets in Childhood Epilepsy

Abstract: Metabolic effects of a new ketogenic regimen in which ketonemia is induced by feeding of medium chain triglycerides (MCT) are described, and comparisons are made with effects of the standard high fat ketogenic diet. Eighteen children maintained on the MCT diet for 3 months to 4 years failed to show elevations of serum cholesterol and had only a slight rise in serum total fatty acids, in contrast to the marked hyperlipidemia observed in children on the standard high fat diet. Long term use of the MCT diet did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
242
3
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(254 citation statements)
references
References 7 publications
4
242
3
5
Order By: Relevance
“…Earlier studies performed in patients on the diet have failed to show any specific relation between success of diet with systemic changes induced by the diet, for example, pH, electrolytes, or cholesterol (4)(5)(6). In particular, the level of serum ketones does not specifically relate to degree of seizure control, although it has been shown that with resumption of a normal diet or by a glucose infusion, there is rapid loss of seizure control (6,7). Thus although ketosis is a requirement for seizure control, it is not the defining factor.…”
mentioning
confidence: 99%
“…Earlier studies performed in patients on the diet have failed to show any specific relation between success of diet with systemic changes induced by the diet, for example, pH, electrolytes, or cholesterol (4)(5)(6). In particular, the level of serum ketones does not specifically relate to degree of seizure control, although it has been shown that with resumption of a normal diet or by a glucose infusion, there is rapid loss of seizure control (6,7). Thus although ketosis is a requirement for seizure control, it is not the defining factor.…”
mentioning
confidence: 99%
“…Unfortunately, tests did not bear it out. In clinical studies, Huttenlocher 9 showed that the ketogenic diet did not make the blood acidic, and Al-Mudallal et al 10 later showed in animal studies that the ketogenic does not change the pH of either the blood or the brain.…”
Section: The Ph Hypothesismentioning
confidence: 99%
“…Glucose is still present in the blood of patients on the ketogenic diet, usually in the low normal range. 9,13 This glucose is presumably entering into the brain and being used for energy. Even after some weeks of complete starvation, fats provide only about 60% of the brain's energy supply.…”
Section: The Increased Brain Energy Hypothesismentioning
confidence: 99%
“…Elaborou-se uma tabela de freqüência das crises epilépticas para cada paciente, confrontando-a, em seguida, com a análise da freqüência de todos os tipos de crises de cada um, realizando, assim, um estudo comparativo e, por fim, utilizaram-se os seguintes critérios de Huttenlocher 7 …”
Section: Resposta Clínicaunclassified